Mode I and Mode II fracture assessment of green asphalt pavements containing plastic waste and RAP at low and intermediate temperature - Baradaran, Sajed; Aliha, M. R. M. (Elsevier, 2025)
This study aimed to assess the cracking resistance of an asphalt mixture incorporating a PET-based additive (PBA) obtained from recycled Polyethylene Terephthalate (PET) and a high proportion of reclaimed asphalt pavement (RAP) at low and intermediate temperatures under various fracture modes (pure mode I and II) to achieve two significant aims means to reduce harmful effects of accumulation of PET wastes and design resistant pavement. This study blended PBA in different dosages (1-3 %) with asphalt binder. RAP was added to the asphalt mixture in different content (25 and 50 % aggregate weight). After fabricating cylindrical specimens corresponding to the various mixture types, SCB specimens were obtained from cylindrical specimens. Fracture tests were conducted in different loading conditions regarding different fracture modes at low and intermediate temperatures. Results demonstrate that adding PBA to asphalt pavement can increase cracking resistance at low and intermediate temperatures in different fracture modes. Moreover, based on the results across various indices and under different loading and temperature conditions, adding up to 25 % RAP to the mixture interacts effectively with PBA, leading to increased crack resistance. Among all tested mixtures, the combination of 2 % PBA and 25 % RAP yielded the best performance. Comprehensive statistical analysis also confirms the results of this study in both modes of fracture and temperature conditions.
Keywords: Polyethylene terephthalate (PET); Recycling; Reclaimed asphalt pavement (RAP); Pure modes I & II; Low and intermediate temperatures; Low and intermediate temperatures